Characteristics and functions of glyceraldehyde 3-phosphate dehydrogenase S-nitrosylation during controlled aging of elm and Arabidopsis seeds. (9th July 2021) - Zeng, MeiYan; He, YuQi; Gao, Xue; Wang, Yu; Deng, ShiMing; Ye, TianTian; Wang, XiaoFeng; Xue, Hua
Abstract: Seed aging is the gradual decline in seed vigor, during which programmed cell death (PCD) occurs. The functions of nitric oxide (NO) are exerted through protein S -nitrosylation, a reversible post-translational modification. During seed aging, more than 80 proteins are S -nitrosylated, but the particular role of individual proteins is unknown. Here, we showed that the S -nitrosylation level of glyceraldehyde 3-phosphate dehydrogenase (UpGAPDH) in elm ( Ulmus pumila L.) seeds increased after controlled deterioration treatment. UpGAPDH was S -nitrosylated at Cys154 during S -nitrosoglutathione (GSNO) treatment, and its oligomerization was triggered both in vitro and in elm seeds. Interestingly, UpGAPDH interacted with the mitochondrial voltage-dependent anion channel in an S -nitrosylation-dependent way. Some UpGAPDH–green fluorescent protein in Arabidopsis protoplasts co-localized with mitochondria during the GSNO treatment, while the S -nitrosylation-defective UpGAPDH C154S–GFP protein did not. Seeds of oxUpGAPDH lines showed cell death and lost seed vigor rapidly during controlled deterioration treatment-triggered seed aging, while those overexpressing S -nitrosylation-defective UpGAPDH-Cys154 did not. Our results suggest that S -nitrosylation of UpGAPDH may accelerate cell death and seed deterioration during controlled deterioration treatment. These results provide new insights into the effects of UpGAPDH S -nitrosylation on protein interactions and seed aging. Abstract : Glyceraldehyde 3-phosphate dehydrogenase S -nitrosylation induced oligomerization and interaction with the mitochondrial voltage-dependent anion channel, which may function in cell death and loss of seed vigor during deterioration of seeds.